2004
DOI: 10.1007/s10267-004-0201-0
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical study on the interaction between the root endophytic fungus Heteroconium chaetospira and Chinese cabbage

Abstract: Chinese cabbage roots colonized by the dematiaceous fungal taxon Heteroconium chaetospira were previously found to become highly resistant to clubroot and Verticillium yellows. The dematiaceous fungus possesses an endophytic nature, but no detailed anatomical studies on endophyte-host plant interactions have so far been provided. Light and electron microscopy revealed that hyphae of H. chaetospira were abundant on and inside the root epidermal cells by 3 weeks following inoculation. The penetration pegs easily… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 9 publications
(11 reference statements)
0
19
0
Order By: Relevance
“…A number of detailed microscopy studies on the infection process by this endophyte have been undertaken (Ohki et al, 2002;Yonezawa et al, 2004) where it was observed that, in the root tip region of B. napus and B. rapa plants, the fungus produced an appressoria-like structure on the cell surface before entering and colonising cortical cells. No visible signs of host reactions and no invagination of the host plasma membrane around hyphae were seen (Yonezawa et al, 2004) and the endophyte subsequently formed distinctive structures made from aggregations of mycelium (microsclerotia) inside the host epidermal roots Ohki et al, 2002). Beneficial attributes for the host plant, conferred by the endophyte, include plant growth promotion and reduced disease symptoms caused by a number of pathogens including Alternaria spp., P. brassicae, Pseudomonas syringae pv.…”
Section: Fungal Endophytesmentioning
confidence: 99%
See 2 more Smart Citations
“…A number of detailed microscopy studies on the infection process by this endophyte have been undertaken (Ohki et al, 2002;Yonezawa et al, 2004) where it was observed that, in the root tip region of B. napus and B. rapa plants, the fungus produced an appressoria-like structure on the cell surface before entering and colonising cortical cells. No visible signs of host reactions and no invagination of the host plasma membrane around hyphae were seen (Yonezawa et al, 2004) and the endophyte subsequently formed distinctive structures made from aggregations of mycelium (microsclerotia) inside the host epidermal roots Ohki et al, 2002). Beneficial attributes for the host plant, conferred by the endophyte, include plant growth promotion and reduced disease symptoms caused by a number of pathogens including Alternaria spp., P. brassicae, Pseudomonas syringae pv.…”
Section: Fungal Endophytesmentioning
confidence: 99%
“…Researchers investigating the biology of this fungus often use baiting techniques, such as planting seedlings of Chinese cabbage, barley, rape or rhododendron in soils suspected of harbouring the endophyte (Narisawa et al, , 1998 with woodland, field and forest soils in Japan and Canada, found to be favourable so far (Usuki and Narisawa, 2007). A number of detailed microscopy studies on the infection process by this endophyte have been undertaken (Ohki et al, 2002;Yonezawa et al, 2004) where it was observed that, in the root tip region of B. napus and B. rapa plants, the fungus produced an appressoria-like structure on the cell surface before entering and colonising cortical cells. No visible signs of host reactions and no invagination of the host plasma membrane around hyphae were seen (Yonezawa et al, 2004) and the endophyte subsequently formed distinctive structures made from aggregations of mycelium (microsclerotia) inside the host epidermal roots Ohki et al, 2002).…”
Section: Fungal Endophytesmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, no defense responses were found when the interaction between T. aestivum and M. bolleyi was studied with TEM, only an electronically dense material was observed around the intercellular hyphae. This is similar to fibrillar material observed surrounding the hyphae in Chinese cabbage in the presence of Heteroconium chaetospira (Yonezawa et al, 2004) and in Asparagus officinalis inoculated with P. fortinii (Yu et al, 2001). Although in the current study the fibers were not observed, it could be due to an inefficient fixation of the material.…”
Section: Interaction With Wheatmentioning
confidence: 42%
“…The ability of H. chaetospira to colonize and grow as an endophyte in healthy roots has been demonstrated previously using Chinese cabbage (Ohki et al 2002;Yonezawa et al 2004;Hashiba and Narisawa 2005) and rhododendron (Usuki and Narisawa 2005); these studies were based on isolates obtained from soil samples from Japan baited with herbaceous plants. There were prior reports of this species from the roots of Ammophila arenaria (L.) Link collected in the UK (IMI 60911) (Domsch et al 1980) and a smaller-278 spored variety, described by Bourchier as Septonema chaetospira var.…”
Section: Discussionmentioning
confidence: 94%